Lamination process of second generation high temperature superconducting tape at Shanghai Superconductor Technology. (June 2022) - Zhu, Jiamin; Zhao, Yue; Chen, Sikan; Zhen, Shuiliang; Zhang, Chao; Song, Bai; Sheng, Jie; Wu, Wei; Jin, Zhijian
Abstract: As the second generation high temperature superconducting (HTS) tape enters the stage of commercialization and mass production, it has been successfully applied in several power and magnet devices. Different application scenarios also put forward different requirements for the electrical and mechanical properties of the HTS tape. This paper focuses on introducing the post-processing treatments of HTS tape, primarily copper plating and lamination. By preparing typical samples, the properties of copper-plated tapes and laminated tapes have been experimentally compared. The results show that under the condition of sufficient liquid nitrogen flow, the steady-state over-current tolerance of copper-laminated tape is significantly better than that of stainless steel-laminated and copper-plated tapes. At the same room temperature resistance, the over-current impact tolerance of stainless steel-laminated tape is 2–3 times that of copper-plated tape; the maximum transient current beared by the tapes reached 3896 A when they were put under shock for 8 ms, which has significant advantages in the application of resistive fault current limiter. At 77 K, yield strength Rp0.2 of the three types of superconducting tapes are > 1100 MPa for stainless steel-laminated tape, 645–1037 MPa for copper-plated tape and < 500 MPa for copper-laminated tape. The critical tensile stress of stainless steel laminated-tape is higher than that of copper-plated tape and copper-laminated tape. The tape reinforced structure described in this paper can provide a helpful reference for future design and manufacture of superconducting applications in power and magnet industries. Graphical Abstract: ga1